Differential expression of genes involved with apoptosis, cell cycle, connective tissue proteins, fuel substrate utilization, inflammation, and mitochondrial biogenesis in copper-deficient rat hearts: Implication of a role for Nfkb1. - Ricklefs, Kristen; Klaahsen, Darcey; Medeiros, Denis M. (My University, 2007)
We hypothesized that the increase in mitochondrial proliferation in hearts from copper-deficient rats is due to an increase in expression of the transcriptional factor Ppargc1a, which regulates transcriptional activity for many of the genes that encode for mitochondrial proteins. In addition to several transcriptional factors implicated in mitochondrial biogenesis, we also looked at a number of genes involved in cell cycle regulation and fuel substrate utilization. Long-Evans rats were placed on either a copper-adequate (n=4) or copper-deficient (n=4) diet 3 days post-weaning and remained on the diet for five weeks; their copper deficiency status was confirmed using previously established assays. Custom oligo arrays spotted with genes pertinent to mitochondrial biogenesis were hybridized with cRNA probes synthesized from the collected heart tissue. Chemiluminescent array images from both groups were analyzed for gene spot intensities and differential gene expression. Our results did not demonstrate any significant increase in Ppargc1a or its implicated targets, as we had predicted. However, consistent with previous data, an up-regulation of genes that encode for collagen type 3, fibronectin and elastin were found. Interestingly, there was also a significant increase in the expression of the transcriptional factor Nf kappa b1 in the copper-deficient treatment animals compared to the control group. The results of this study merit the further investigation of the role of ROS with regard to Nf kappa b1 in the copper deficient rat heart.
Keywords: Copper-deficiency; Rats; Heart; Mitochondrial Nf kappa b1; Ppargc1a